1982
DOI: 10.1111/j.1469-8986.1982.tb02529.x
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary Dilation as an Index of the Orienting Reflex

Abstract: The effects of tone intensity (60, 75, or 90 dB) on the amplitude and habituation of the pupillary dilation response were investigated using a between‐groups design (N = 72). Although pupillary dilation responses were elicited in all intensity conditions, neither response amplitude nor habituation was influenced by differences in stimulus intensity, and the response was insensitive to changes in intensity following the habituation series. Eighteen subjects in the 90dB group were retested and the reliability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 4 publications
(3 reference statements)
3
34
0
Order By: Relevance
“…Although various sound-containing stimuli induce pupillary dilation, effects are nominal (19) or very brief (1) and show rapid habituation (1,19,61). Notably, one study failed to detect dilation at decibel levels comparable with that used in this study (53).…”
Section: Discussionmentioning
confidence: 55%
“…Although various sound-containing stimuli induce pupillary dilation, effects are nominal (19) or very brief (1) and show rapid habituation (1,19,61). Notably, one study failed to detect dilation at decibel levels comparable with that used in this study (53).…”
Section: Discussionmentioning
confidence: 55%
“…Pupillometry, the measurement of change in the size of the pupil, has been used as a measure of effort in psychology (Laeng, Sirois, & Gredebäck, 2012;see Loewenfeld, 1993, for a review), with the pupil becoming larger as more cognitive effort is exerted. Evidence for this has been shown in larger pupil sizes being measured when the experimental stimuli presented were more intense (Stelmack & Siddle, 1982) and with increased memory load (Beatty, 1982;Granholm, Asarnow, Sarkin, & Dykes, 1996;Kahneman, 1973;Kahneman & Beatty, 1966). In the context of the Stroop task, it has been shown that the diameter of the pupil is largest during incongruent trials, relative to both neutral (Laeng et al, 2011) and nonword neutral (G. G. Brown et al, 1999) trials, which in turn elicit larger pupil diameters than congruent trials (Siegle, Steinhauer, & Thase, 2004).…”
Section: Pupillometry As a Measure Of Effortmentioning
confidence: 99%
“…Subsequent studies have repeatedly shown that pupil size variations are positively correlated to the intensity of the stimulus (e.g., tones varying in dB; Stelmack and Siddle 1982) or the difficulty of the task (e.g., increasing load on memory; Kahneman and Beatty 1966). One of the first applications of pupillometry to psycholinguistics was conducted by Just and Carpenter (1993) who demonstrated that pupil diameter changed in reading as a function of sentence complexity.…”
Section: Introductionmentioning
confidence: 98%